Evaluation of Fat and Vitamin E in Some Cookies Diet - Al-Shawabkeh, Ali F.; Mazahreh, Ayman S. (Pakistan Journal of Nutrition, 2009)
This study was carried out on 5 different products from 3 different firms: Digestive Biscuit, Biscuit with fiber, Biscuit without Sugar but with fiber, Toast bread, Toast Bread without salt. Vitamin E, moisture and fat was evaluated by analysis. At the beginning of the study the content of vitamin E, in mg/100g dry matter in the five products from three different firms, respectively, were 3.16, 2.86, 2.84 and the average was 2.96. Moisture percentages were: 3.97, 3.70, 3.52 the average was 3.73 and fat% was: 10.96, 11.63, 11.75, the average was 11.45. At the end of the storage period (6 months), the content of vitamin E was 2.30, 1.64, 1.81, the average 1.92. Moisture was 5.52, 5.50 and 5.19. The average was 5.40. It may be concluded that 35.47% of vitamin E were lost during the storage period.